2006
DOI: 10.1021/es051972f
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Probability of Arsenic in Groundwater in New England as a Tool for Exposure Assessment

Abstract: We developed a process-based model to predict the probability of arsenic exceeding 5 microg/L in drinking water wells in New England bedrock aquifers. The model is being used for exposure assessment in an epidemiologic study of bladder cancer. One important study hypothesis that may explain increased bladder cancer risk is elevated concentrations of inorganic arsenic in drinking water. In eastern New England, 20-30% of private wells exceed the arsenic drinking water standard of 10 micrograms per liter. Our pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 37 publications
3
124
0
Order By: Relevance
“…As expected, the coexistence of rocks with slow kinetics of arsenic release and short residence time of groundwater generates relatively low arsenic concentrations, as reported in other regions of the world (e.g., [63]). The influence of residence time on arsenic content of sampled groundwater is clear from the comparison between the distribution in the basal aquifer and in the perched aquifers or dome-impounded groundwater (Figure 4): in the entire hydrogeological system, the lowest arsenic contents were found in the sources, mainly springs located at high elevation, where the short flow path from recharge to discharge area implies a reduced water-rock interaction (Figure 3).…”
Section: Discussionsupporting
confidence: 81%
“…As expected, the coexistence of rocks with slow kinetics of arsenic release and short residence time of groundwater generates relatively low arsenic concentrations, as reported in other regions of the world (e.g., [63]). The influence of residence time on arsenic content of sampled groundwater is clear from the comparison between the distribution in the basal aquifer and in the perched aquifers or dome-impounded groundwater (Figure 4): in the entire hydrogeological system, the lowest arsenic contents were found in the sources, mainly springs located at high elevation, where the short flow path from recharge to discharge area implies a reduced water-rock interaction (Figure 3).…”
Section: Discussionsupporting
confidence: 81%
“…These models resulted in a 75% agreement, NPV=0.85, PPV=0.53, sensitivity =0.62−0.63, and specificity=0.80. In comparison, an arsenic regression model built for the New England area resulted in lower sensitivity (0.37) and higher specificity (0.93) using 5 μg/L as the cut-off value (Ayotte et al, 2006). NPV and PPV were not reported in the New England study, but were estimated from the data provided as NPV=0.83, and PPV=0.60, similar to what we report in this paper using a higher cut-off value (10 μg/L).…”
Section: Discussionmentioning
confidence: 93%
“…Alternative approaches are available, such as land-use regression (Ayotte et al, 2006) and Classification and Regression Trees (CART) (Schroder, 2006), in which spatial variables are classified into distinct categories and used to predict a dependent variable (e.g., arsenic) in a-spatial analyses. These approaches fail to explicitly consider the spatial pattern or proximity of the dependent variable, but rather take advantage of regionally available factors, such as geology, land use/cover, and hydrology in making predictions (Ayotte et al, 2006). Factors that vary greatly from well to well, however, such as well depth, are often difficult to estimate at unsampled locations, and therefore challenging to include in these predictive models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used SAGA-GIS (SAGA Development Team, 2008) to calculate the following DEM derived parameters: (1) Topographic Wetness Index (TWI), (2) Catchment slope, (3) Topographic index, (4) Modified Catchment Area (MCA), (5) Slope and (6) Elevation. These variables can correlate with hydrologic processes of the aquifer (Ayotte et al, 2006). Studies in Cambodia and Bangladesh revealed that there is a strong correlation between topographic environmental variables and the content of As in groundwater (Rodríguez-Lado et al, 2008;Shamsudduha et al, 2009).…”
Section: Topographic Variablesmentioning
confidence: 99%